Portrayal of an ascetic figure - Temples of India Project Team (Jio Institute, 2024)
In an alternative portrayal of the ascetic, he is depicted standing, facing slightly to his left. He has a jatabhara (matted hairdo) atop his head and a lengthy moustache. The features of his face have eroded, but two notable ones are his elongated earlobes and the rudraksha (dried stones or seeds of the Elaeocarpus ganitrus associated with Shiva iconography) armband. One of his hands clasps a pot while his fingers are delicately positioned atop it. Notably, his phallus is exposed in this depiction.